Advances in library administration and organization. Volume 33 - Williams, Delmus Eugene; Golden, Janine; Sweeney, Jennifer K. (Emerald, 2015)
Volume 33 of Advances in library administration and organization will look at different challenges library administrators encounter, review emerging trends and bring critical analysis to this area. The last volume edited by Delmus E. Williams, Janine Golden and Jennifer Sweeney brings together a range of diverse and reflective essays to provide strategies that will be of value in addressing challenges faced by current and future librarymanagers. The first chapter of this volume looks at incorporating human resources development (HRD) into the strategic planning of libraries. Continuing on from this, Jon E. Cawthorne examines the ways research libraries can use new organizational models to support library services. A case study by Denise Kwan and Libi Shen recognizes skills identified in libraries as contributing to successful leadership. Next is a different kind of piece about efforts to link a library information course to a learning community with a focus on teaching English as a Second Language (ESL). Finally, architect Peter Gisolfi argues that library buildings will need to adapt as they transition to community information centers.
Keywords: Library administration.; elektronické knihy; electronic books